Cardiac Hydatid Cyst and Rhythm Disorders: Unusual Manifestations of a Rare Disease - Zerhoudi, Rim; Ztati, Mohamed; Hamdouli, Nouhaila; Yahya, Abdekarim Ait; El Jamili, Mohammed; Elhattaoui, Mustapha (British Journal of Healthcare and Medical Research, 2024)
Introduction: Hydatid cyst is a parasitic disease endemic in various regions of the world. Pulmonary and hepatic involvement are the most described lesions. Cardiac localization remains rare, accounting for only 0.5 to 2% of all cases [1]. The aim of our study was to present a rare case in which a hydatid cyst was diagnosed following an episode of ventricular tachycardia. Case report: We report the case of a 49-year-old patient with no modifiable cardiovascular risk factors, presenting with sudden-onset palpitations lasting 24 hours prior to admission, accompanied by NYHA class II dyspnea on exertion. Clinical examination revealed a hemodynamically and respiratory stable patient, without signs of heart failure. The admission ECG showed epicardial ventricular tachycardia (180 bpm, wide QRS at 206 ms, right-axis deviation, and TV score = 4). After vagal maneuvers and adenosine failed, intravenous amiodarone successfully achieved pharmacological cardioversion. Post-cardioversion ECG revealed sinus rhythm with negative T waves in lateral leads. Transthoracic echocardiography identified a probable extracardiac mass (88 × 24 mm) near the left ventricle and atrium, with preserved cardiac function and no pericardial effusion. Thoracic CT confirmed extracavitary cystic formations, including an intramyocardial cyst suggestive of hydatid cysts. Biological tests, including hydatid serology, were negative, and extension imaging (chest X-ray and abdominal ultrasound) found no anomalies. Cardiac MRI confirmed three calcified cystic masses: a 63 × 27 mm intramyocardial mass near the lateral LV wall, a 14 × 12 mm pericardial cyst, and a 7 × 6 mm epicardial cyst, all consistent with hydatid cysts. The patient declined any surgical intervention and was placed on medical therapy comprising Albendazole and Cordarone for rhythm control. The clinical course was complicated by the occurrence of electrical storm, ultimately leading to the patient's death. Discussion et Conclusion: Cardiac hydatid cysts are a rare condition with diverse clinical manifestations but potentially serious outcomes. The diagnosis is significantly facilitated using echocardiography. In the absence of truly effective therapeutic alternatives, cystectomy and pericystectomy, performed with or without obliteration of the residual cavity, remain the only surgical interventions offering a chance for recovery with an acceptable morbidity and mortality rate.